Settlement of Pusako-Tinggi Property Disputes in Nagari Sungai Tarab - Dodon Alfiander; Ikhsan Azhari; Irma Suryani (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This article examines the decision of the Batusangkar District Court Number 09/Pdt.G/2013 which authorizes the Nagari Adat Density (KAN) of Sungai Tarab to resolve disputes over the division of pusako-tinggi assets, while KAN does not yet have a clear norm regarding it. This study aims to see how KAN accepts the delegation of authority, then resolves disputes in its customary territory with all its implications. This study was conducted qualitatively and presented descriptively. Data obtained through interviews and documentation. This paper explains that the division of the pusako-tinggi assets by KAN Sungai Tarab is carried out with a consensus mechanism by niniak mamak and alim ulama, so that their decisions do not conflict with Islamic law. The status of the pusako-tinggi property is decided to remain in the ownership of the clan, except for parts that have been certified and have changed status to become the private property of clan members. This decision has a positive impact in the form of more clarity on the management and ownership of the people of property. While the negative impact is triggering members of other clans to demand a similar pattern of inheritance distribution, as well as efforts to disgrace each other to fight over inheritance.